Kitab Fiqh Al-Akbar Karya Imam Abu Hanifah - Achmad Sopian (Indonesia, 2021)
Abu Hanifah (80H-150H) is one of the figures who made valuable contributions to the development of Islamic law. His legal thought more advanced aspects of rationality that is affected by geographic and demographic environment of Iraq. Many progressive thinking and different from other scholars, both on methodological aspects and results of ijtihad.Al-Fiqh al-Akbar (big fiqh) is the only monograph work of Imam Abu Hanifah who was instrumental in developing the school of fiqh he built. Therefore, reviewing Abu Hanifah's fiqh paradigm cannot be separated from the discourse contained in it. Unlike fiqh works in general which contain comprehensive legal dictums, al-fiqh al-Akbar actually elaborates a lot on the science of monotheism. For Abu Hanifah, the idea of ​​kalam is very important to embody the principles of faith contained in the Qur'an. While the law is nothing but the relation of the science of kalam which is directly in touch with the deeds of the mukallaf. Human actions are judged to have kasbi nature so that they have room to adjust to the Qur'an and Hadith. It is this perspective of the Qur'an and the deeds of the mukallaf that later colors every phrase in the work of al-Fiqh al-Akbar. This study discusses the book of Fiqh al-Akbar by Imam Abu Hanifah using the library research method, in analyzing the data this method uses a descriptive analysis model. As a source of information, namely; scientific books, research reports, scientific articles and journals. From the results of this study, it can be explained that the work of Imam Abu Hanifah has made a major contribution to Islamic scholarship today with the existence of al-Fiqh al-Akbar which reviews the science of kalam.